THE DETERMINATION AND APPRECIATION OF PROFESSIONAL MICROCLIMATE AT A WORKPLACE - Oana CHIVU; Claudiu BABIS; Andrei DIMITRESCU; Dan Florin NIŢOI (Fiabilitate şi Durabilitate)
The microclimate at work is a very important element that puts a mark on worker health. The paper presents the methodology for determining and appreciating the professional microclimate through its components: air temperature; Relative air humidity; Airflow velocity; Caloric radiation; The working surface temperature at work. The aim of the paper is to educate in order to obtain an appropriate microclimate to avoid overworking of the visual analyzer, stimulate higher nerve activity processes, increase working capacity, prevent occupational diseases, work accidents and chronic fatigue